Clinical assessment of arterial stiffness with cardio-ankle vascular index: theory and applications. Issue 9 (September 2015) - Hayashi, Kozaburo; Yamamoto, Tomoyuki; Takahara, Akira; Shirai, Kohji
Abstract : Arterial stiffness is often assessed in clinical medicine, because it is not only an important factor in the pathophysiology of blood circulation but also a marker for the diagnosis and the prognosis of cardiovascular diseases. Many parameters have so far been proposed to quantitatively represent arterial stiffness and distensibility, such as pressure–strain elastic modulus ( E p ), stiffness parameter ( β ), pulse wave velocity (PWV), and vascular compliance ( C v ). Among these, PWV has been most frequently applied to clinical medicine. However, this is dependent on blood pressure at the time of measurement, and therefore it is not appropriate as a parameter for the clinical evaluation of arterial stiffness, especially for the studies on hypertension. On the contrary, stiffness parameter β is an index reflecting arterial stiffness without the influence of blood pressure. Recently, this parameter has been applied to develop a new arterial stiffness index called cardio-ankle vascular index (CAVI). Although this index is obtained from the PWV between the heart and the ankle, it is essentially similar to the stiffness parameter β, and therefore it does not depend on blood pressure changes during the measurements. CAVI is being extensively used in clinical medicine as a measure for the evaluation of cardiovascular diseases and risk factors related to arteriosclerosis. In the present article, we will explain the theoretical background of stiffness parameter β and the process to obtain CAVI. And then, the clinical utility of CAVI will be overviewed by reference to recent studies.